A Comparation Of Chinese And Indonesian Time Adverbs - Ying, Yi (Bina Nusantara University, 2012)
Chinese time adverbs describe status of behavior, modal frequency, or that the behavior has occurred, occurred in the past, present or future. When describe a time, it usually emphasizes the meaning. Indonesian time adverbs describe an event or action occurred at a time. It indicates the status of behavior, modal or indicates whether the conduct has occurred, has not happened, will happen, repeat and describe the act or thing is not yet completed. This study attempts to shed light on why students incline to make mistake in using Chinese time adverbs. Furthermore, students face difficulty in differentiating between Chinese and Indonesian time adverbs. Chinese Indonesia have the similar meaning of time adverb, such as: gang, yijing, cengjing, zhengzai, jiang, hai, mashang but function in a sentence not exactly same.